2017
DOI: 10.1016/j.fertnstert.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovary morphology: age-based ultrasound criteria

Abstract: Objective To determine age-based criteria for polycystic ovary morphology. Design The study was a cross sectional, case-control design. Setting The study took place in an outpatient setting. Subjects Women with PCOS defined by hyperandrogenism and irregular menses (n=544) and controls with regular menses and no evidence of hyperandrogenism (n=666) participated. Parameters were tested in a second cohort of women with PCOS (n=105) and controls (n=32) meeting the same criteria. Interventions Subjects unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
3
8
0
2
Order By: Relevance
“…Does it really matter? When the data from Quinn et al's study are well observed, the decrease in the diagnostic threshold is relatively small between the 25‐30 and 30‐35 age groups, as recently reported by others for AMH and AFC, whereas it becomes much sharper for the group between 35 and 40 years. The same is true for interquartile range (IQR), whose width after age adjustment is much larger in the latter group than in the other two.…”
supporting
confidence: 64%
“…Does it really matter? When the data from Quinn et al's study are well observed, the decrease in the diagnostic threshold is relatively small between the 25‐30 and 30‐35 age groups, as recently reported by others for AMH and AFC, whereas it becomes much sharper for the group between 35 and 40 years. The same is true for interquartile range (IQR), whose width after age adjustment is much larger in the latter group than in the other two.…”
supporting
confidence: 64%
“…Moreover, PCOM in the diagnosis of PCOS continues to be a matter of debate because the presence of PCOM appears to be age related . Kim et al described that the ovarian volume and follicle number threshold to define PCOM should be lowered starting at age 30 . Furthermore, the identification of PCOS following menopause remains problematic, because there are no established diagnostic criteria of serum androgens levels or intensity of hirsutism in elderly women and the ovarian morphology changes dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age in the United States, with research showing that about 5% to 18% of females between 18 and 44 affected with the disorder . PCOS involves defects in the hypothalamic‐pituitary axis, insulin secretion and action, and ovarian function, which can lead to elevated androgen levels, menstrual irregularities, and/or increased follicular number and volume in one or both ovaries . Increased insulin levels cause ovarian overproduction of androgens, leading to anovulation …”
Section: Introductionmentioning
confidence: 99%
“…1,2 PCOS involves defects in the hypothalamic-pituitary axis, insulin secretion and action, and ovarian function, which can lead to elevated androgen levels, menstrual irregularities, and/or increased follicular number and volume in one or both ovaries. 1,3,4 Increased insulin levels cause ovarian overproduction of androgens, leading to anovulation. 1,5 Women with PCOS are predisposed to higher rates of cardiovascular disease, obesity, dyslipidemia, hypertension, impaired glucose tolerance, type 2 diabetes mellitus, and endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%